Musculoskeletal Pain Is Associated with Dietary Diversity Score among Community-Dwelling Older Adult: A Cross-Sectional Study - Zahra Tajary; Zahra Esmaeily; Mahshid Rezaei; Shahrzad Daei; Atefeh Eyvazkhani; Marjan Mansouri Dara; Ahmad Reza Dorosty Motlagh (International Journal of Food Science)
Background. Musculoskeletal pains (MSP) are the most common cause of long-term severe pain and physical disability among older adults. This study is aimed at determining the relationship between dietary diversity score (DDS) and MSP in Tehran’s older adults. Methods. The study was a cross-sectional one that employed 213 participants with and without MSP complaints between May and October 2019 in Tehran, Iran. A 100 mm length visual analog scale questionnaire was used to assess pain along with a validated 147-item food frequency questionnaire for DDS evaluation. Statistical analyses included descriptive analysis and multiple linear regression with a significance level of p<0.05. Results. 85% of the participants had a range of MSP with a low but insignificant DDS compared to individuals without pain (p=0.12, 3.24 ±0.86 vs. 3.43 ±0.85, respectively). A significant association was observed among the quartiles of DDS that most of the subjects with MSP were in the lowest quartile relative to the highest one (p=0.02). Moreover, the association between DDS and MSP remained significant in the adjusted model (OR=0.28, 95%CI=0.08−0.99). Conclusion. A high-quality diet is important. Our study showed that a higher dietary diversity might be associated with lower MSP in older adults. More robust interventional studies are thus warranted to confirm the results.